SISTEM INFORMASI INVENTORY BERBASIS DOTNET ( STUDI KASUS TOKO SINGAPORE SHOES TEMBILAHAN) - Usman, Usman; Zainuddin, Zainuddin (SISTEMASI, 2016)
Singapore Shoes is a store that sells shoes, handbags, wallets and other accessories. Inventory system is a very important part in the operator of an enterprise, manufacturing inventory system affects the level of income and corporate earnings. Therefore, companies have to actually supervise and control the activities of sales, purchase and supply of goods by implementing an adequate system, so the system inventory can be managed properly. With the above considerations required an application inventory system capable of managing the supply of stocks in order to improve the quality of service so that the transaction manager to the management of the inventory can be done effectively and efficiently exist in Singapore Shop Shoes Tembilahan. The design of these applications use the design diagram UML (Unified Modeling Language) and programming language C # using Visual Studio 2010. Keywords: Information Systems Inventory, Unified Modeling Language (UML), Visual Studio C# 2010.